Q: 6x2 plus 32x plus 12-4x-3x2-36

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

6x2 + 11x + 3 = 6x2 + 9x + 2x + 3 = 3x(2x + 3) + 1(2x + 3) = (2x + 3)(3x + 1)

2x(3x + 5)

-3x3 - 6x2 + 189x = -3x(x2 + 2x - 63) = -3x(x + 9)(x - 7)

6x2+ 35xy + 11y2=6x2+ 33xy + 2xy + 11y2= 3x(2x + 11y) + y(2x + 11y)= (2x + 11y)*(3x + y) 6x2+ 35xy + 11y2=6x2+ 33xy + 2xy + 11y2= 3x(2x + 11y) + y(2x + 11y)= (2x + 11y)*(3x + y) 6x2+ 35xy + 11y2=6x2+ 33xy + 2xy + 11y2= 3x(2x + 11y) + y(2x + 11y)= (2x + 11y)*(3x + y) 6x2+ 35xy + 11y2=6x2+ 33xy + 2xy + 11y2= 3x(2x + 11y) + y(2x + 11y)= (2x + 11y)*(3x + y)

4x2-x+2x2 is 6x2-x when simplified

Related questions

9+6x2=21

6x2 + 10x = 2x(3x + 5)

6x2=12 2x-28=?

No.

6x2 + 7x - 5 = (3x + 5)(2x - 1)

(3x+1)(2x+4) = 6x2+4+2x+12x = 6x2+14x+4

6x2-18x+12 = (6x-6)(x-2)

6x2-17x+7 = (2x-1)(3x-7) when factored

yes.it is.

6x2 + 64x - 12 = 10 ∴ 6x2 + 64x - 22 = 0 ∴ 3x2 + 32x - 11 = 0 ∴ 3x2 + 33x - x - 11 = 0 ∴ 3x(x + 11) - 1(x + 11) = 0 ∴ (3x - 1)(x + 11) = 0 ∴ x ∈ {1/3, -11}

(3x+1)(2x+2)

Simplifying 6x2 + 23x + 7 Reorder the terms: 7 + 23x + 6x2 Factor a trinomial. (7 + 2x)(1 + 3x) Final result: (7 + 2x)(1 + 3x)